Extended distribution and host plants of Nameriophyes sapidae Xue & Zhang 2008 (Acari: Eriophyidae) in New Zealand - Martin, Nicholas A.; Zhang, Zhi-Qiang (Zootaxa, 2011)
Nameriophyes sapidae Xue & Zhang (Acari: Eriophyidae) was found on transplanted nikau palms, Rhopalostylis sapida (H. Wendl. & Drude) in Auckland, New Zealand and described as a new species (Xue & Zhang 2008). Although R. sapida is a native plant species, it was not known if this mite species was indigenous or adventive because it was collected only from transplanted palms in unnatural gardens in Auckland. A survey was undertaken of R. sapida and the Kermadec Island palm, Rhopalostylis baueri (Hook. f.) Wendl. & Drude in the northern part of the North Island and Chatham Island.